Hypersensitivity to metallic implants: pathophysiologic and diagnostic considerations - Kounis, Nicholas G; Koniari, Ioanna (Acta Biomedica Atenei Parmensis, 2018)
Metals are ubiquitous in the surrounding environment and constitute an important class of substances that can act as allergens. Consumer products such as earings, zip, jewellery, cosmetics, paints, dental and body implants as well as endovascular, intracardiac and orthopedic devices are made from metals. Metal anions eluted from various metals are common allergic sensitizers. In Europe nickel, chromium and cobalt induce allergic skin reactions in about 20%, 4%, and 7% while in the United States14%, 4%, and 9% respectively